Sources of forage adjusted to temperature changes for wintering cows in drylot - McKee, M.; Kimple, K.; Ames, D.R.; Willms, C.L.; Corah, L.R. (Kansas State University. Agricultural Experiment Station, 2011)
Cows in mid-to-late gestation gained weight when fed either milo stover silage or alfalfa hay-wheat straw but lost weight when the forage source was milo-stover bales. When supplemented with additional corn grain as temperature decreased, cows receiving milo stover stilage or alfalfa hay-wheat straw gained more eight, and cows receiving milo stover bales lost less weight than cows receiving the same forages but fed to NRC (1976) requirements.
Cattlemen's Fate in '78 is known as Cattlemen’s Day, 1978
Keywords: Beef; Temperature; Drylot; Forage